PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA ANGGOTA SATUAN POLISI PAMONG PRAJA KOTA CIREBON - Ardika Nurfurqon (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2020)
This study aims to determine the effect of Compensation and Job Satisfaction on Employee Performance in the City of Cirebon Civil Service Police Unit. With a quantitative approach, it was found that employee compensation has been high, where 71.46% of respondents stated that they received high compensation. Job satisfaction is in the high category, where 68.82% of respondents said they were satisfied. Employee performance is in the high category, where 69.81% of respondents carry out work that is their responsibility properly. Work compensation and satisfaction along with its dimensions have a positive and significant effect on employee performance. This gives an understanding that the more intensive the provision of compensation and efforts to increase job satisfaction, the more performance of the civil service police organization.